Step-by-step Solution

Solve the equation $\frac{2x+6}{2}-x=3$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

true

Step-by-step Solution

Problem to solve:

$\frac{2x+6}{2}-x=3$
1

Combine $\frac{2x+6}{2}-x$ in a single fraction

$3=3$
2

$3$ equals to $3$

true

Final Answer

true
$\frac{2x+6}{2}-x=3$

Main topic:

Equations

Time to solve it:

~ 0.03 s

Related topics:

EquationsPrecalculus